(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A person's natural condition is referred to as their Prakriti. According to Ayurveda, each individual is assigned a certain Prakriti, which is created by the Tridosha present at the moment the sperm and ovum unite inside the uterus. An individual's Prakriti is determined by the dominance of any one, two, or all three Doshas (the three bodily humors: Vata, Pitta, and Kapha). Therefore, the word "Prakriti" refers to an individual's genetically determined anatomical, physiological, and psychological constitution. Prakriti is one of the oldest conceptions of preventative, personalized, or genetic medicine since it also predicts how an individual will react to pharmaceuticals, the environment, and their vulnerability to certain diseases. Vikriti, which refers to a person's ill state, stands in opposition to Prakriti. Because abnormality cannot be detected until the normal is understood, Prakriti is crucial in defining Vikriti. In order to understand the nature and severity of the disease, the body's response to the drugs (pharmacogenomics), the selection of the drugs and their doses, the prognosis of the disease, and preventive measures such as diet, diurnal and seasonal regimes, Acharya Charaka have mentioned Dashavidha Pariksha. Therefore, Prakriti places a strong emphasis on uniqueness, and is crucial to diagnosis, preventative medicine, and treatments.